The effects of geopolitical uncertainties on growth: Econometric analysis on selected Turkic Republican countries and neighboring states - Halil İbrahim Aydin; Aniela Bălăcescu; Genu Alexandru Căruntu (Economies, 2025)
The paper aims to analyze the effect of geopolitical uncertainties on growth in the countries of selected Turkic republics and neighboring states which are experiencing geopolitical uncertainty, especially regarding their position in the global economy. This study investigates how uncertainties quantified by geopolitical risk indices for the global economy (GE), the United States (US), and the Russian Federation (RS) influence the economic growth of the Turkic republics and neighboring states which implement open macroeconomic policies. This analysis employs panel data techniques that consider the interdependence between cross-sectional units. The selected countries included in the study are Azerbaijan, Kazakhstan, Kyrgyzstan, Tajikistan, Turkey, Turkmenistan, Mongolia, and Uzbekistan. The results show the existence of constricting effects on the economic growth performance of selected countries.
Keywords: 330; geopolitical uncertainties; economic growth; panel NARDL; Turkic republics and neighboring states